Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                
0% found this document useful (0 votes)
61 views3 pages

Double Pendulum Modeling

Download as pdf or txt
Download as pdf or txt
Download as pdf or txt
You are on page 1/ 3

Double Pendulum Modeling

Huei Ee YAP
Graduate School of Advanced Science and Engineering, Waseda University
55N-4F-10A, 3-4-1 Okubo, Shinjuku-ku, Tokyo, 169-8555, Japan
huei@shalab.phys.waseda.ac.jp

May 31, 2012

Force and Moment Equations

Figure 1: The schematic of double pendulum


l1 sin1
x1 =
l1 cos1


l1 cos1 1
x 1 =
l1 sin1 1


l2 sin(1 + 2 )
x2 = x1 +
l1 cos(1 + 2 )


l2 cos(1 + 2 )(1 + 2 )
x 2 = x 1 +
l2 sin(1 + 2 )(1 + 2 )

Kinetic energy and potential energy of system


1 T
1
x m1 x 1 + x T2 m2 x 2
2 1
2
1
1
= m1 (l1 cos1 1 )2 + m1 (l1 sin1 1 )2
2
2

2
1
+ m2 l1 cos1 1 + l2 cos(1 + 2 )(1 + 2 )
2

2
1
+ m2 l1 sin1 1 + l2 sin(1 + 2 )(1 + 2 )
2
1
1
= m1 l12 12 cos2 1 + m1 l12 12 sin2 1
2
2


1
+ m2 l12 cos2 1 12 + l22 cos2 (1 + 2 )(1 + 2 )2 + 2l1 l2 cos1 cos(1 + 2 )1 (1 + 2 )
2


1
+ m2 l12 sin2 1 12 + l22 sin2 (1 + 2 )(1 + 2 )2 + 2l1 l2 sin1 sin(1 + 2 )1 (1 + 2 )
2
1
1
1
= m1 l12 12 + m2 l12 12 + m2 l22 (1 + 2 )2 + m2 l1 l2 1 (1 + 2 )cos2
2
2
2
U = (m1 + m2 )gl1 cos1 m2 gl2 cos(1 + 2 )
T =

The Lagrangian of the system is hence


L=T U
1
1
= (m1 + m2 )l12 12 + m2 l22 (1 + 2 )2 + m2 l1 l2 1 (1 + 2 )cos2
2
2
+ (m1 + m2 )gl1 cos1 + m2 gl2 cos(1 + 2 )

L
= (m1 + m2 )l12 1 + m2 l22 (1 + 2 ) + 2m2 l1 l2 cos2 1 + m2 l1 l2 cos2 2
1
d L
= (m1 + m2 )l12 1 + m2 l22 (1 + 2 ) 2m2 l1 l2 sin2 1 2
dt 1
+ 2m2 l1 l2 cos2 1 m2 l1 l2 sin2 2 + m2 l1 l2 cos2 2
2

L
= (m1 + m2 )gl1 sin1 m2 gl2 sin(1 + 2 )
1
L
= m2 l22 (1 + 2 ) + m2 l1 l2 cos2 1
2
d L
= m2 l22 1 + m2 l22 2 m2 l1 l2 sin2 1 2 + m2 l1 l2 cos2 1
dt 2
L
= m2 l1 l2 1 (1 + 2 )sin2 m2 gl2 sin(1 + 2 )
2
The equations of motion is

(m1 + m2 )l12 + m2 l22 + 2m2 l1 l2 cos2 1 + (m2 l22 + m2 l1 l2 cos2 )2
2m2 l1 l2 sin2 1 2 m2 l1 l2 sin2 22 + (m1 + m2 )gl1 sin1 + m2 gl2 sin(1 + 2 ) = 1
(m2 l2 + m2 l1 l2 cos2 )1 + m2 l2 2 + m2 l1 l2 sin2 1 + m2 gl2 sin(1 + 2 ) = 2
2

Putting into standard manipulator equation:


q + G(q) = B(q)u
H(q)
q + C(q, q)
we have

H(q) =

=
C(q, q)

G(q) =

B(q) =

(m1 + m2 )l12 + m2 l22 + 2m2 l1 l2 cos2

m2 l22 + m2 l1 l2 cos2

m2 l22 + m2 l1 l2 cos2

m2 l22

2m2 l1 l2 sin2 2

m2 l1 l2 sin2 2

m2 l1 l2 sin2

(m1 + m2 )gl1 sin1 + m2 gl2 sin(1 + 2 )


m2 gl2 sin(1 + 2 )
1

where q = [1 , 2 ]T and u = [1 , 2 ]T

References

You might also like